2023
DOI: 10.3390/su15064944
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Chilean Native Species in Vertical Greening Systems

Abstract: Vertical greening systems (VGSs), i.e., living walls (LWs) and green façades (GFs), are considered a promising technology to diminish the negative effects of urbanisation. Plant selection for these systems is challenging due to the narrow spectrum of species available, and the required adaptation to specific climate conditions. Considering Chile’s rich plant biodiversity, this study aims to analyse the potential of Chilean native species to be introduced in VGSs. A total of 109 potentially usable species from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…While the major parts of the studies took place in the formal landscapes in recent years that were registered in terms of public spaces such as parks, open spaces, and natural resources [21], the evidence showed that informal and small green spaces such as vertical gardens, kitchen gardens, decorative plants, follower boxes [26], and native plants [27] include benefits for social interactions even in temporal forms [4]. As a piece of evidence, Tafahomi [18] highlighted that both private and public landscapes contribute to the urban temperature and cooling of the buildings in three different layers, including green spaces in courtyards, trees in liner forms alongside streets to provide shading for buildings, and the climber vines and shrubs to cover walls.…”
Section: Introductionmentioning
confidence: 99%
“…While the major parts of the studies took place in the formal landscapes in recent years that were registered in terms of public spaces such as parks, open spaces, and natural resources [21], the evidence showed that informal and small green spaces such as vertical gardens, kitchen gardens, decorative plants, follower boxes [26], and native plants [27] include benefits for social interactions even in temporal forms [4]. As a piece of evidence, Tafahomi [18] highlighted that both private and public landscapes contribute to the urban temperature and cooling of the buildings in three different layers, including green spaces in courtyards, trees in liner forms alongside streets to provide shading for buildings, and the climber vines and shrubs to cover walls.…”
Section: Introductionmentioning
confidence: 99%